Triphenylamine-Based Push-Pull Molecule for Photovoltaic Applications: From Synthesis to Ultrafast Device Photophysics - Kozlov, Oleg V.; Liu, Xiaomeng; Luponosov, Yuriy N.; Solodukhin, Alexander N.; Toropynina, Victoria Y.; Min, Jie; Buzin, Mikhail I.; Peregudova, Svetlana M.; Brabec, Christoph; Ponomarenko, Sergei A.; Pshenichnikov, Maxim S. (Journal of Physical Chemistry C, 2017)
Small push-pull molecules attract much attention as prospective donor materials for organic solar cells (OSCs). By chemical engineering, it is possible to combine a number of attractive properties such as broad absorption, efficient charge separation, and vacuum and solution processabilities in a single molecule. Here we report the synthesis and early time photophysics of such a molecule, TPA-2T-DCV-Me, based on the triphenylamine (TPA) donor core and dicyanovinyl (DCV) acceptor end group connected by a thiophene bridge. Using time-resolved photoinduced absorption and photoluminescence, we demonstrate that in blends with [70]PCBM the molecule works both as an electron donor and hole acceptor, thereby allowing for two independent channels of charge generation. The charge-generation process is followed by the recombination of interfacial charge transfer states that takes place on the subnanosecond time scale as revealed by time-resolved photoluminescence and nongeminate recombination as follows from the OSC performance. Our findings demonstrate the potential of TPA-DCV-based molecules as donor materials for both solution-processed and vacuum-deposited OSCs. (Figure Presented). © 2017 American Chemical Society.
Keywords: Charge transfer; Molecules; Organic solar cells; Photoluminescence; Solar cells; Vacuum applications; Charge separations; Independent channels; Interfacial charge transfer; Photoinduced absorption; Photovoltaic applications; Push-pull molecules; Subnanosecond time scale; Time-resolved photoluminescence; Synthesis (chemical)